Review of Recent Advances in Intelligent and Antibacterial Packaging for Meat Quality and Safety - Junjun Zhang; Jianing Zhang; Lidan Zhang; Zhou Qin; Tianxing Wang (Foods)
Intelligent and antimicrobial packaging technologies are transforming meat preservation by enhancing food safety, enabling real-time quality monitoring, and extending shelf life. This review critically examines advancements in intelligent systems, including radio frequency identification (RFID), gas sensors, time-temperature indicators (TTIs), and colorimetric indicators for continuous freshness assessment. A key focus is natural compound-based chromogenic indicators, which establish visual spoilage detection via distinct color transitions. Concurrently, antimicrobial systems integrating inorganic compounds, organic bioactive agents, and natural antimicrobials effectively inhibit microbial growth. Strategic incorporation of these agents into polymeric matrices enhances meat safety, supported by standardized evaluation protocols for regulatory compliance and quality assurance. Future research should prioritize optimizing sensitivity, cost-efficiency, and sustainability, alongside developing biodegradable materials to balance food safety with reduced environmental impact, advancing sustainable food supply chains.